From illegitimate disruption to failing state : how South African newspapers framed 'service delivery' protests in 2013 - Pointer, Rebecca (Centre for Film and Media Studies, 2015)
This study unpacks the key frames and sources used by the South African print media in their coverage of the ‘service delivery protests’ in 2013. It explores how the frames are linked to each other, how the sources link to each other, and how the frames and sources correlate. The study focuses on print media sources as catalogued in the SA Media database, identifies the most prevalent frames and sources used, and using a hierarchical cluster analysis identifies how frames are related to each other, how sources are related to each other, and how frames and sources correlate. The study found that the most prevalent frames on ‘service delivery protests’ used by the South African print media in 2013 were the war/spectacle frame and the failed democracy frame, followed by the law/crime frame, all of which serve to delegitimise service delivery protests. Local government and police sources were most prevalent. The study suggests that there is still contestation about the kinds of spaces citizens should use for political engagement, and contestation about how power operates at local government level. The media also implies that the South African state is failing, and suggests remedies for these failings.